Using Cloze Strategy to Improve Students’ Reading Comprehension - Zulianti, Hajjah; Wiratno, Purna; Novia, Siska (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
The objective of this research was to improve students’ reading comprehension and their learning activities by using the Cloze Strategy. In this research, the writer used Classroom Action Research as the design of the research. This research was implemented in two cycles. The sample of this research was 30 students. To get the data, the writers used observation sheet and a reading test. The test used in this research was a closed-end question, which consisted of 25 questions. The test was aimed at getting the score of the students’ reading comprehension; meanwhile, an observation sheet was used to find out the students’ learning activities. The result of the test showed that there was an improvement of the students’ reading abilities and learning activities. It was found that the students’ reading ability in cycle 1 was 57.07 while in cycle 2 was 80.53, and it was found that the score of the students’ learning activities in cycle 1 was 6.19 while in the cycle 2 was 7.85. Therefore, the implementation of the Cloze Strategy was successful to be used in improving the students’ reading comprehension and the students’ learning activities.